Cytokine profile in surgical treatment of chronic generalized periodontitis - M. I. Kuzmin; O. V. Tsymbalov; L. V. Akopova (Кубанский научный медицинский вестник)
During complex surgical treatment of chronic generalized periodontitis studies were taken concerning the production of interleukin 1β in the periphery blood and mixed saliva. A close connection was noticed between the level of cytokine production, stage of the disease and the treatment effectiveness: straight dependence with IL-1β, so its concentrations could be an objective diagnostic markers.